Decreased Numbers of CD4+ Naive and Effector Memory T Cells, and CD8+ Naïve T Cells, are Associated with Trichloroethylene Exposure - Hosgood, H Dean (Frontiers in Oncology, 2012)
Trichloroethylene (TCE) is a volatile chlorinated organic compound that is commonly used as a solvent for lipophilic compounds. Although recognized as an animal carcinogen, TCE’s carcinogenic potential in humans is still uncertain. We have carried out a cross-sectional study of 80 workers exposed to TCE and 96 unexposed controls matched on age and sex in Guangdong, China to study TCE’s early biologic effects. We previously reported that the total lymphocyte count and each of the major lymphocyte subsets (i.e., CD4+ T cells, CD8+ T cells, natural killer (NK) cells, and B cells) were decreased in TCE-exposed workers compared to controls, suggesting a selective effect on lymphoid progenitors and/or lymphocyte survival. To explore which T lymphocyte subsets are affected, we investigated the effect of TCE exposure on the numbers of CD4+ naïve and memory T cells, CD8+ naïve and memory T cells, and regulatory T cells by FACS analysis. Linear regression of each subset was used to test for differences between exposed workers and controls adjusting for potential confounders. We observed that CD4+ and CD8+ naïve T cell counts were about 8% (p = 0.056) and 17% (p = 0.0002) lower, respectively, among exposed workers. CD4+ effector memory T cell counts were decreased by about 20% among TCE exposed workers compared to controls (p = 0.001). The selective targeting of TCE on CD8+ naïve and possibly CD4+ naive T cells, and CD4+ effector memory T cells, provide further insights into the immunosuppression-related response of human immune cells upon TCE exposure.